Multikinase inhibitors sorafenib and sunitinib as radiosensitizers in head and neck cancer cell lines. Issue 4 (21st February 2017) - Affolter, Annette; Samosny, Gerson; Heimes, Anne‐Sophie; Schneider, Johanna; Weichert, Wilko; Stenzinger, Albrecht; Sommer, Katharina; Jensen, Alexandra; Mayer, Arnulf; Brenner, Walburgis; Mann, Wolf J.; Brieger, Jürgen
Abstract: Background: Radioresistance is a common feature of head and neck squamous cell carcinoma (HNSCC). We previously showed that the irradiation‐ activated vascular endothelial growth factor (VEGF)‐extracellular signal‐regulated kinase (ERK)‐axis is fundamental for the survival of resistant tumors. In this study, we examined if treatment with potent multikinase (MK) inhibitors, sorafenib and sunitinib, could radiosensitize tumor cells. Methods: Cultured HNSCC cell lines were treated with inhibitors and subsequently irradiated. Radiosensitizing effects were functionally assessed by annexin‐V apoptosis and clonogenic assays and confirmed by Western blot. Additionally, we surveyed human HNSCC tissue microarrays (TMAs) for activated ERK expression. Results: Based on combination indexes, we found that combining irradiation with both inhibitors exerted strong and supra‐additive antitumor effects on clonogenic survival. Kinase inhibition enhanced irradiation‐induced apoptotic rates and inhibited postradiogenic phospho‐ERK‐expression. Patients with recurrent HNSCC displayed significantly lower extracellular signal‐regulated kinase phosphorylation (pERK) levels than relapse‐free patients. Conclusion: We propose further evaluation of sorafenib and sunitinib as potential radiosensitizing agents in HNSCC treatment. © 2017 Wiley Periodicals, Inc. Head Neck 39: 623–632, 2017